ANALISIS PERAN LITERASI FINANSIAL DAN PERSEPSI PROSPEK KARIR TERHADAP KEPUTUSAN MAHASISWA MEMILIH PROGRAM STUDI DI UIN PONOROGO - Kholiq, Abdul; Abror, Ima Nur; Huda, Muhamad Nurul; Lutviana, Mia; Khoirulhuda, Muhamad Satrio; Rosyid, Muhamad Muhktar (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the role of financial literacy and career prospect perception in students’ decision-making processes when choosing a study program at UIN Kiai Ageng Muhammad Besari Ponorogo. The data were collected through semi-structured interviews with students from various faculties using a qualitative approach and a case study method. The results show that financial literacy plays a crucial role in students' consideration of tuition costs, daily expenses, and long-term educational investments. Students with higher financial awareness tend to make more rational and measured decisions. Additionally, career prospect perception significantly influences students' motivation and confidence in selecting a major. Students who perceive strong career opportunities in their field of study are more optimistic and goal-oriented. Overall, the decision to choose a study program is shaped by a combination of internal and external factors, including economic conditions, access to information, personal interests, and long-term career goals.